2020
DOI: 10.5334/gh.793
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Involvement in Chagas Disease and Insulin Resistance: A Non-Metabolic Model of Cardiomyopathy

Abstract: Background: Heart failure (HF) and type 2 Diabetes Mellitus (T2DM) represent two chronic interrelated conditions accounting for significant morbidity and mortality worldwide. Insulin resistance (IR) has been identified as a risk factor for HF; however, the risk of IR that HF confers has not been well elucidated. The present study aims to analyze the association between myocardial involvement in Chronic Chagas Cardiomyopathy (CCM) and IR, taking advantage of this non-metabolic model of the disease. Methods: Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Many factors may be involved in the risk of developing chronic Chagas heart disease and/or megasyndromes including age, sex, geographical origin, parasite load, genetic heterogeneity of T. cruzi and its discrete typing units (DTU, TcI–TcVI), immunological aspects of the host, severity of the initial acute infection, transmission route, exposure to T. cruzi reinfection in areas with sustained vector transmission, nutritional status, presence of comorbidities, and the social context and quality of life of CD patients [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may be involved in the risk of developing chronic Chagas heart disease and/or megasyndromes including age, sex, geographical origin, parasite load, genetic heterogeneity of T. cruzi and its discrete typing units (DTU, TcI–TcVI), immunological aspects of the host, severity of the initial acute infection, transmission route, exposure to T. cruzi reinfection in areas with sustained vector transmission, nutritional status, presence of comorbidities, and the social context and quality of life of CD patients [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 176 Muitos fatores estão envolvidos no risco de progressão da FIDC para a CCDC, tais como: idade; sexo masculino; origem geográfica; intensidade da carga parasitária; cepa do T. cruzi e suas “ discrete typing units ” (TcI–TcVI e Tc-bat); aspectos genéticos do hospedeiro; gravidade da infecção aguda inicial relacionada com a via de transmissão; exposição à reinfecção pelo parasito em áreas com transmissão vetorial sustentada; estado nutricional e presença de comorbidades; contexto social; qualidade de vida dos indivíduos com DC; e ausência de tratamento antiparasitário. 247 , 297 , 510 - 517 …”
Section: Condutas Terapêuticas Na Forma Indeterminada Da Doença De Ch...unclassified
“… 176 Several factors are involved in the risk for IFCD progression to CCCD, such as: age; male sex; geographical origin; parasite load intensity; T. cruzi strain and its discrete typing units (TcI–TcVI and Tc-bat); host’s genetic aspects; severity of the initial acute infection related to the transmission mode; exposure to reinfection with the parasite in sustained vectorial transmission areas; host’s nutritional status and presence of comorbidities; social context; quality of life of individuals with CD; and absence of trypanocidal treatment. 247 , 297 , 510 - 517 …”
Section: Therapeutic Management In the Indeterminate Form Of Chagas D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac fat tissue (epicardial and pericardial fat tissue) is located in proximity to heart muscle and probably plays an important role in regulating cardiac parasite load, inflammation, and metabolic functions [10]. Clinical studies have shown an association between body mass index (BMI), fat mass, dyslipidemia, nutritional status, and CCC severity [11,12]. However, it is not known whether adipocytes directly regulate the pathogenesis of CCC.…”
Section: Introductionmentioning
confidence: 99%